Constelações de aprendizagem nas práticas da Umbanda no terreiro Mãe Oxum e Pai Ogum - Santos, Thais Rodrigues dos (2018)
The present research aims to investigate the educational processes about Umbanda’s practices in the Mother Oxum’s and Pai Ogum’s spiritual center (terreiro) at Irati-PR, Brazil, from the concept of learning constellations (SILVA, 2016). The theoretical-methodological perspective is based on the texts of Fredrik Barth (2000) and Manuela Carneiro da Cunha (2009) on ethnic interactions and cultural boundaries, as well as the discussion of the anthropology of education as a possibility of dialogue with traditional Afro-Brazilian knowledge. In this learning scenario, the bond to the ancestry in the Mother Oxum and Pai Ogum’s terreiro in learning with the seniority, collectivity, matricentrality and religiosity to model the elements of the constellation, whose dynamics establish the time and the learning experience for each member. From the experience of ethnography, the importance of the medium's participation, above all, of the cambonoes is the condition of their belonging and access to the community knowledge for the development of their ancestral bond in response to mediumship development. Since the mediumship of the members needs to be learned in the community relationship with the sacred, elders and other holy sons of the community.